ANOREXIA E BULIMIA EM ADOLESCENTES - Carvalho, Paula Virgínia Lisbôa Chaves de (2008)
This is a cross-sectional study whose objectives are to investigate the occurrence of possible eating disorders, anorexia and/or bulimia in adolescents of both sexes, and to identify the epidemiologic profile of both. To identify eating disorders, 500 adolescents from a private school in São Luís, Maranhão, Brazil, completed self-report questionnaires, the BITE (Bulimic Investigatory Test Edinburgh) and the EAT-26 (Eating Attitudes Test summarized). The findings indicate that 70 (14%) adolescents possibly present with diagnoses of anorexia, 4 (0,8%) of bulimia, and 11(2,2%) with anorexia and bulimia combined. It was observed that 78 (15,6%) adolescents presented with non-usual eating habits, placing them at risk for the development of eating disorders. This investigation shows that there is a high occurrence of possible eating disorders in the sample studied and a heterogeneous epidemiologic profile, occurring in both sexes and within diverse ethnic groups and social-economic classes. The dissatisfaction with their own bodies and the wish to modify them are feelings present in adolescents who probably exhibit eating disorders (p<0.001).